New zeolite-like RUB-5 and its related hydrous layer silicate RUB-6 structurally characterized by electron microscopy - Krysiak, Yaşar; Marler, Bernd; Barton, Bastian; Plana-Ruiz, Sergi; Gies, Hermann; Neder, Reinhard B; Kolb, Ute (IUCrJ, 2020)
This study made use of a recently developed combination of advanced methods to reveal the atomic structure of a disordered nanocrystalline zeolite using exit wave reconstruction, automated diffraction tomography, disorder modelling and diffraction pattern simulation. By applying these methods, it was possible to determine the so far unknown structures of the hydrous layer silicate RUB-6 and the related zeolite-like material RUB-5. The structures of RUB-5 and RUB-6 contain the same dense layer-like building units (LLBUs). In the case of RUB-5, these building units are interconnected via additional SiO4/2 tetrahedra, giving rise to a framework structure with a 2D pore system consisting of intersecting 8-ring channels. In contrast, RUB-6 contains these LLBUs as separate silicate layers terminated by silanol/sil-oxy groups. Both RUB-6 and RUB-5 show stacking disorder with intergrowths of different polymorphs. The unique structure of RUB-6, together with the possibility for an interlayer expansion reaction to form RUB-5, make it a promising candidate for interlayer expansion with various metal sources to include catalytically active reaction centres.
Keywords: stacking faults; electron crystallography; microporous materials; inorganic materials; diffuse scattering; exit wave reconstruction; framework-structured solids; computational modelling; 3D electron diffraction; polymorph prediction